PENDAMPINGAN KEWIRAUSAHAAN DI PONDOK PESANTREN SIROJUT THOLIBIN TELUK DALEM MATARAM BARU LAMPUNG TIMUR - huri, Daman; Jamiluddin Yacub; Pipit Apipah (LPPM STAI DARUSSALAM LAMPUNG, 2022)
The largest increase in unemployment occurred in the young group aged 20-29 years. Currently, the number of youth (aged 16-30 years) is 64.50 million. Of that amount, 17.66% of youth aged 20-24 years and 9.27% ​​youth aged 25-29 years are unemployed. Since 2010, the government has launched the National Entrepreneurship Movement, which aims to create new entrepreneurs. The movement is a cross-ministerial program in the form of entrepreneurship campaigns, public education, training, funding, and coaching. In addition, the Indonesian government has also required entrepreneurship learning in every university. The purpose of this service is to foster entrepreneurial spirit, motivation, and creativity and to equip students with the right knowledge in making business plans, while the results of entrepreneurship mentoring activities generally go well, this can be seen from the growth of students' thinking, motivation and creativity. Then the students after participating in the mentoring can prepare a new business plan that will be developed by the students at the Sirojut Tholibin Islamic Boarding School. This assistance will foster the spirit of the importance of the entrepreneurial spirit that needs to be fostered for intellectual youth at this time, to reduce the large gap between the number of the workforce and the number of jobs